Thinking differently: lessons learned by international public health specialists while supporting the Integrated Disease Surveillance and Response system in Pakistan. Issue 10 (13th October 2020) - Wilson, Anne; Cartwright, Christopher
Abstract : Internationally supported activities to build public health capacity and improve compliance with International Health Regulations (2005) so that countries are better able to ' prevent, protect against, control and provide a public health response to the international spread of disease ' have had a positive impact in recent years. However, despite the proliferation of technical guidance, tools and roadmaps, as the recent COVID-19 emergency demonstrates, a significant challenge still remains. The unique and complex environment within countries is increasingly being recognised as a factor which needs greater consideration if system strengthening activities are to be successful. This paper reflects on the learning from and charts out the journey of the authors' in their efforts to support the Pakistan government to improve compliance with International Health Regulations, specifically through strengthening its Integrated Disease Surveillance and Response (IDSR) system. To effect change, public health technical specialists bring their grounded technical and scientific expertise along with their softer public health skills of, among other things, relationship building and multisector working. In the authors' experience, the importance of taking time throughout to build and maintain strong trusted relationships and peer-to-peer support has been the key to the successes experienced. The nature of this relationship and ongoing reflexive dialogue enabled the co-construction of the reality of the background environment, which, in turn, led to more realistic visioning of the desired system for IDSR, and therefore more appropriate bespoke technical support to be given, leading to the design and initial implementation of a country owned system developed with sustainability in mind.